Tanggung Jawab Debitur Dalam Perjanjian Kredit Tanpa Agunan (KTA) Pada Koperasi Serba Usaha (KSU) Kuta imba Kabupaten Badung - Dewa Ayu Putu Mita Purnamasari; I Nyoman Putu Budiartha; Desak Gde Dwi Arin (Jurnal Interpretasi Hukum, 2021)
Unsecured credit facilities (KTA) at the Kuta Mimba Business Multipurpose Cooperative (KSU) in Badung Regency can ease the burden on people who want to be entrepreneurs, because there is no material guarantee. The purpose of this study is to determine the arrangement if the debtor is declared in default at the Multipurpose Business Cooperative (KSU) Kuta Mimba, Badung Regency and to know the debtor's responsibilities in the unsecured credit agreement (KTA) at the Multipurpose Business Cooperative (KSU) Kuta Mimba, Badung Regency. This research was conducted at KSU Kuta Mimba in Badung Regency. This type of research uses empirical legal research, namely a problem approach that is seen in terms of legal rules with the realities that exist in the field. The results of the research obtained that the arrangement if the debtor is declared in default is regulated in the Loan Agreement articles 6 and 7 which regulate the rights and obligations of the borrower and the lender. The responsibility of the creditor to the debtor in the unsecured credit agreement (KTA) is first done by visiting the debtor to the house with the aim of asking what is the reason for not paying the credit, the second is doing by rescheduling.